Poder político na Câmara dos Deputados: sobre distributivismo, seus reflexos eleitorais e Teoria do Controle - Tarcisio Augusto Sousa de Barros (2017)
This research is about distortions of political power, its electoral implications and a Theory of Control in the Brazilian Chamber of Deputies. The central objective of the work is to analyze the abuse of power practiced during the course of the parliamentary mandate and its influence in electoral campaigns for reelection, and, therefore, to present an attempt to control such phenomenon. To do so, the study was subdivided into three chapters. In the first part of Barry Ames's book, The Obstacles to Democracy in Brazil, we address the main objectives of Federal Representatives in their mandates and how they act for action. In the second chapter, we study the impacts and influences of the distributivist parliamentary activity in the book Electoral Constitutional Principles, by Eneida Desiree Salgado. In the third, we refrain relevant aspects from the Theory of the Control of the Power, in Theory of the Constitution and Democratic Constitutional Law, respectively of Karl Loewenstein and Rodolfo Viana Pereira, and their importance for the democratic constitutionalism; then, we present an alternative for oxygenation of the Brazilian Parliament to reduce the particularist character of the electoral campaigns for the Chamber of Deputies.